Social Community Engagement: The Evidence of the Muslim Youth Movement of Malaysia (ABIM) (Journal of Business Management and Accounting, 2017)
The social engagement by the Non-Governmental Organisation (henceforth, NGO) reflects social accountability to the public. With this in mind, the paper examines the role of social disclosures in articulating NGO accountability relations in ABIM. The conceptual framework of this paper delineates social accountability, which can be explained from the perspective of financial accountability into social actions that are delineated from verbal conversations, conducts and body language. In line with this, the paper addresses an initial exploration by framing moral positioning within NGO accountability relations through a social context in accounting. The empirical contribution is obtained from a case study of ABIM, employing interpretive methodology, through a series of in-depth interviews and documentary reviews. The empirical evidence reveals the accounting mechanisms by highlighting the values of a well-defined Islamic community in public policy debate. The NGO’s actions, include accounting disclosures, emphasises the moral imperatives underpinning plural rationalities for humanitarian assistance and social movements provided by ABIM.